2014
DOI: 10.1142/s0219877014500072
|View full text |Cite
|
Sign up to set email alerts
|

Business Models in the Commercialization Processes of Innovation Among Small High-Technology Firms

Abstract: Small technology firms are currently facing increasingly severe competition in a dynamic business environment where an effective commercialization process may secure the survival of a venture and provide key benefits such as increases in turnover, profits and market share. However, technology firms have to be able to create the suitable business model for a new product commercialization in order to realize the economical potential and value. Therefore, it is important to increase our knowledge about the utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This confirms the importance of developing innovation management from market studies and sustaining it with successful business strategies. 18,28,34,46 Finally, the incidence of the intellectual property management, recognized by Hsueh and Chen, 47 as part of innovation management was also confirmed, although this was the perspective of less impact. 48,49 The major contributions of this research are focused on two aspects.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This confirms the importance of developing innovation management from market studies and sustaining it with successful business strategies. 18,28,34,46 Finally, the incidence of the intellectual property management, recognized by Hsueh and Chen, 47 as part of innovation management was also confirmed, although this was the perspective of less impact. 48,49 The major contributions of this research are focused on two aspects.…”
Section: Discussionmentioning
confidence: 87%
“…This confirms the importance of developing innovation management from market studies and sustaining it with successful business strategies. 18,28,34,46…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercialization involves six channels of entrepreneurial actions leading to sources of innovations, classification of innovation, market capacity, protection, advancement, and deployment (Datta, Reed & Jessup, 2013). Pellikka and Malinen (2014) showed that business models create operative commercialization process which assists individuals to plan the active delivery system through the research and development process phases. Practically and theoretically, commercialization of academics and industry relationship is considered as vital important challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Powell, Koput, and Smith-Doerr (1996) confirm the role of social and relational capital as determinants in the survival of the company on the market in the long term. Relational capital, including the vertically linked delivery chain, is very important in the case of small high-technology companies whose partnerships should strive to find mutually created value as expected by customers (Pellikka and Malinen, 2014).…”
Section: Intellectual Capitalmentioning
confidence: 99%